2018
DOI: 10.1021/acs.jcim.8b00302
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Chemical Space of Known and Readily Obtainable Natural Products

Abstract: Natural products remain one of the most productive sources of chemical inspiration for the development of new drugs. The structures of more than 250 000 natural products are available from public databases. At least 10% of these compounds are readily obtainable for experimental testing from commercial vendors and public research institutions. While the physicochemical properties of known natural products have been thoroughly studied and compared to those of drugs and other types of small molecules, the informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
104
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(117 citation statements)
references
References 49 publications
6
104
0
Order By: Relevance
“…[127][128][129] Meanwhile, the accessibility of this chemicals pace for screening campaigns is low: only about 10 %o ft hese compounds are readily available from commercial vendors and public research institutions. [130] Therefore, the isolation of naturale xtracts,t heir screening, and further identification of active components still remain important strategies of drug discovery. [131] Analysis of new drugs entering the market, according to their registration year (1981-2010) and origin (i.e.,s ynthetic, natural, or modified NP), showed that the number of drugs comingf rom natural sources decreased, to al esser extent, over thesey ears comparedw ith fully synthetic compounds ( Figure 27).…”
Section: Role Of Nps In Drug Discoverymentioning
confidence: 99%
“…[127][128][129] Meanwhile, the accessibility of this chemicals pace for screening campaigns is low: only about 10 %o ft hese compounds are readily available from commercial vendors and public research institutions. [130] Therefore, the isolation of naturale xtracts,t heir screening, and further identification of active components still remain important strategies of drug discovery. [131] Analysis of new drugs entering the market, according to their registration year (1981-2010) and origin (i.e.,s ynthetic, natural, or modified NP), showed that the number of drugs comingf rom natural sources decreased, to al esser extent, over thesey ears comparedw ith fully synthetic compounds ( Figure 27).…”
Section: Role Of Nps In Drug Discoverymentioning
confidence: 99%
“…One of such key contributions has been the organization and analysis of chemical information of NPs, with or without biological activity, in compound databases. Over the past five years, several reviews of NP databases have been published [17][18][19][20][21]. Some of these reviews include chemoinformatic analysis of the contents, diversity, and coverage of the compounds in chemical space.…”
Section: Introductionmentioning
confidence: 99%
“…As part of these synergistic efforts, curated databases of natural products have an important role as they are major tools for data mining, hypothesis generation, and starting points of virtual screening. There are several databases of natural products in the public domain as reviewed recently 3 . Our research group has reported initial efforts to assemble a database of natural products from Mexico called BIOFACQUIM 4 .…”
Section: Introductionmentioning
confidence: 99%